Complexity analysis of human-machine interaction based on principles of axiomatic design - Lo, Shuan (2008)
This research explores the use of Axiomatic Design (AD) concepts for analyzing coupling in human-machine systems. Coupling is a generic shaping factor of complexity, and coupling between user goals and user actions widens the gulf of execution of a human-machine system.